1995
DOI: 10.1074/jbc.270.33.19300
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of ATP on the Binding of the DnaK and DnaJ Chaperones to Each Other, or to Their Various Native and Denatured Protein Substrates

Abstract: Using the native proteins lambda P, lambda O, delta 32, and RepA, as well as permanently unfolded alpha-carboxymethylated lactalbumin, we show that DnaK and DnaJ molecular chaperones possess differential affinity toward these protein substrates. In this paper we present evidence that the DnaK protein binds not only to short hydrophobic peptides, which are in an extended conformation, but also efficiently recognizes large native proteins (RepA, lambda P). The best substrate for either the DnaK or DnaJ chaperone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
86
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 57 publications
8
86
1
Order By: Relevance
“…A DnaJ construct fused to BCCP was immobilized on a sensor chip. Consistent with previous observations (Wawrzynow and Zylicz 1995;Suh et al 1998Suh et al , 1999Laufen et al 1999), a robust interaction was observed when WT DnaK was flowing through the sensor chip in the presence of ATP (Fig. 6a).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…A DnaJ construct fused to BCCP was immobilized on a sensor chip. Consistent with previous observations (Wawrzynow and Zylicz 1995;Suh et al 1998Suh et al , 1999Laufen et al 1999), a robust interaction was observed when WT DnaK was flowing through the sensor chip in the presence of ATP (Fig. 6a).…”
supporting
confidence: 80%
“…ATP hydrolysis may be a natural way to break the dimer during the chaperone cycle. This could be why ATP hydrolysis was observed to be required for productive DnaK-DnaJ interaction (Wawrzynow and Zylicz 1995;Suh et al 1998Suh et al , 1999Laufen et al 1999;Mayer et al 1999). The DnaK-DnaJ interaction is still largely a mystery even after years of extensive efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). A requirement for hydrolyzable ATP for the J-protein-Hsp70 chaperone interaction is well documented (32,36). The ATPase activity of BiP next was significantly enhanced by the JPDI J-domain (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The following observations indicate that our preparation of JPDI J-domain interacts with BiP as its functional partner rather than as an unfolded protein substrate, which also binds to Hsp70 chaperones to stimulate their ATPase activity (11). First, unlike the case for J-protein partners, the binding of unfolded protein substrates to Hsp70 chaperones is inhibited by ATP (36). Second, amino acid replacement of the highly conserved HPD motif with QPD in the J-domain, which commonly causes dysfunction of various J-proteins (35,37), significantly decreased the ability of the JPDI J-domain to bind to BiP and to stimulate its ATPase activity (Figs.…”
Section: Discussionmentioning
confidence: 99%